Cumplimiento de la implementación en la facturación electrónica del sector ferretero en la ciudad de Tunja (2022)
The present work takes electronic invoicing as its main theme, its objective was to analyze compliance with electronic invoicing in the hardware sector of the city of Tunja, taking into account the legal precepts defined in Decree 2242 of November 24, 2015, which establishes guidelines for the implementation, technological progress and evolution of electronic invoicing.